Tecnodiversidade e Ecocivilização: reflorestamentos na China e Brasil - Carvalho Filho, Luciano Goulart de; Rena , Natacha Silva Araújo (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – This study analyzes reforestation initiatives in Brazil and China, exploring their similarities and differences in environmental recovery. The research provides a critical analysis of both countries' efforts in ecosystem restoration, evaluating policies, principles, and methodologies under the concepts of Ecocivilization and Technodiversity.Methodology – The study is based on a bibliographic review of scientific articles and official data on environmental restoration programs in both countries. The comparative approach assesses public policies, investments made, and reforestation models adopted.Originality/relevance – The research highlights the application of Technodiversity and Ecocivilization concepts in the Brazilian context, comparing them with the Chinese experience. It situates itself within the growing BRICS cooperation and its relevance in global sustainability discussions.Results – Findings indicate that China excels in implementing robust public policies for reforestation, while Brazil focuses on biodiversity conservation. The research proposes an integrated approach between the Chinese and Brazilian models, suggesting that Brazil’s conservation experience can be combined with China’s governance structure to optimize large-scale restoration projects.Theoretical/methodological contributions – The study contributes to a broader understanding of reforestation strategies, addressing the intersection of environmental governance, social participation, and sustainable development.Social and environmental contributions – The research emphasizes the importance of community involvement in environmental recovery processes, highlighting how reforestation can strengthen the local economy and create income opportunities. Additionally, the study reinforces the role of reforestation in mitigating climate change and ensuring water and ecological security.
Keywords: Tecnodiversity; Ecocivilization; Afforestation